Networks and states: the global politics of Internet governance - Mueller, Milton (Cambridge, Mass. ; London: MIT Press, 2010)
Mueller identifies four areas of conflict and coordination that are generating a global politics of Internet governance intellectual property, cyber-security, content regulation, and the control of critical Internet resources (domain names and IP addresses). Mueller identifies four areas of conflict and coordination that are generating a global politics of Internet governance intellectual property, cyber-security, content regulation, and the control of critical Internet resources (domain names and IP addresses).